Localized hole states in La₂СиО₄₊δ - Rubin, P.; Sherman, A. (Физика низких температур, 1996)
Bound hole states induced by excess oxygen in La₂СиО₄₊δ are studied in the framework of the extended Hubbard model with the use of the spin-wave approximation. It is shown that the bound states are subdivided into two groups connected with different perturbations introduced by the excess oxygen in an antiferromagnetically ordered crystal. We interpret the two-band structure of the impurity reflectivity spectrum as a manifestation of these two groups of bound states. Calculated binding energies are in agreement with experiment.